Catharsis a second chance for democracy in Malaysia - Ooi, Kee Beng (Strategic Information and Research Development Centre, 2018)
Malaysia pulled itself back from the brink on 9 May 2018. That day the majority of its voting population decided to topple the Barisan Nasional government that had been in power for over 60 years and that had come to be seen as corrupt beyond redemption, and incompetent to boot. Lined up against the unpopular administration of Najib Razak was a coalition led by former strongman Tun Dr Mahathir Mohamad, who at the age of 92 had decided to return to Malaysian politics to stop the rot which many believed had begun during his earlier period in power, in 1981-2003. As the oldest prime minister in world history, he is now setting about creating a structure that he believes will lead to a Malaysia that will achieve the Vision 2020 that he first propounded in 1991. This vision dovetails with the ideals of the highly influential Reformasi Movement which was ignited by the sacking of his deputy, Anwar Ibrahim, in 1998. This compilation of insightful analyses is Ooi Kee Beng's seventh, and discusses key events from the last five years leading up to 9 May 2018 and beyond. These seven books together cover the strange period we may come to know as the Inter-Mahathir Era, and the present volume discusses some of the challenges facing the new government, and the Malaysian population in general, now that the Barisan Nasional has imploded.